SHAKESPEAREAN NEOLOGISMS AND THEIR PECULIARITIES - Ismoilova, Dilorom (Журнал иностранных языков и лингвистики, 2021)
The article discusses the contributions of William Shakespeare to the development of the English speech culture. The author highlights the neologisms of the dramatist and their special features according to the formation.